Selected tax forms, tax evasion, quality of life and the mediating role of information and communication technology: Evidence from Nigeria - YADO, Joy Limaro; OMODERO, Cordelia Onyinyechi (Asian Development Policy Review, 2026)
The research analyzes the implications of specific tax types and tax evasion on the quality of life in Nigeria using income per person as a proxy. It specifically investigates the effects of company income tax, petroleum profit tax, value-added tax, and tax evasion on per capita income (PCI) in Nigeria. The study also examines the moderating role of information and communication technology (ICT) in enhancing the quality of life in Nigeria. Secondary data from 1990 to 2023 is utilized, and Autoregressive distributed lag technique is used and not techniques are employed for analysis. The findings indicate that company income tax and petroleum profit tax have minimal impact on the quality of life in Nigeria. Conversely, value-added tax has a negative and significant effect on income per person in Nigeria. The unintended effect of the shadow economy on PCI is positive at the 10% level, while ICT exerts a considerable positive influence on PCI at the 5% level. In light of these findings, the study recommends a reassessment of VAT policies to ensure alignment with Sustainable Development Goals 1 to 3, given its regressive nature that negatively impacts the nutritional consumption of impoverished households. The Tax Authority should endeavor to utilize OECD strategies to stop Base Erosion and Profit Shifting of multinational corporations operating in Nigeria. Furthermore, the research advocate for more allocation of tax revenue towards infrastructural and ICT development to enhance tax collection and improve living standards, similar to those in developed nations.